Decreased Neuro‐Axonal Proteins in CSF at First Attack of Suspected Multiple Sclerosis. Issue 11 (23rd October 2017) - Stoop, Marcel P.; Runia, Tessel F.; Stingl, Christoph; van der Vuurst de Vries, Roos M.; Luider, Theo M.; Hintzen, Rogier Q.
Abstract : The pathology of multiple sclerosis is located in the central nervous system, therefore cerebrospinal fluid (CSF) is an attractive biofluid for biomarker research for proteins related to the early stages of this disease. In this study, the CSF proteome of patients with a clinically isolated syndrome of demyelination (CIS, a first attack of multiple sclerosis) is compared to the CSF proteome of control patients to identify differentially abundant proteins. CSF samples of 47 CIS patients and 45 control subjects are enzymatically digested and subsequently measured by LC‐MS/MS (LTQ‐Orbitrap). Following mass spectrometry differential abundances of the identified proteins between groups are investigated. A total of 3159 peptides are identified, relating to 485 proteins. One protein is significantly more abundant in CSF of CIS patients than in controls: Ig kappa chain C region. In contrast, 35 proteins are significantly lower in CIS patients than controls, most of them with functions in nervous system development and function, such as amyloid‐like protein 1 (validated by ELISA in an independent sample set ( p  < 0.01)), contactin 1, contactin 2 and neuronal cell adhesion molecule. A remarkably lower abundance of neuro‐axonal proteins is observed in patients with a first demyelinating event compared to controls.